Andragogi: Adaptasi Pembelajaran Orang Dewasa Pada Era Digitalisasi - ade saputra saputra; Dewi wulandari fahrezi; Afriza Afriza (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
It is these facilities that can help individuals become more willing to do new things, to be bold and brave, to be able to try new things with new people, and to be willing to share new information that has been learned, making them essential learning environments. Generating a kesalahan is not impossible when learning something new, but the kesalahan and kekeliruan itself are aspects that are understandable in education. Eventually, the old people became disillusioned with their goals and joined a learning group. Those in their later years frequently have the desire to express their kelebihan and kekurangannya. For this reason, it is very important for groups to work together in a comprehensive manner to conduct joint evaluations that can be used as reflective materials. This will enable groups to evaluate each other based on the opinions of other people. The field of education is seeing rapid changes, one of which is the rise of online learning. Digital literacy is declining.